2011
DOI: 10.1186/1471-2407-11-364
|View full text |Cite
|
Sign up to set email alerts
|

A Nation-Wide multicenter 10-year (1999-2008) retrospective clinical epidemiological study of female breast cancer in china

Abstract: BackgroundAccording to the very limited cancer registry, incidence and mortality rates for female breast cancer in China are regarded to be increasing especially in the metropolitan areas. Representative data on the breast cancer profile of Chinese women and its time trend over years are relatively rare. The aims of the current study are to illustrate the breast cancer profile of Chinese women in time span and to explore the current treatment approaches to female breast cancer.MethodsThis was a hospital-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
239
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(252 citation statements)
references
References 23 publications
(21 reference statements)
8
239
4
1
Order By: Relevance
“…A similar trend was observed in the tumor stage distribution. By convention, TNM stages I and II are classified as early breast cancer stages (Li et al, 2011). We found that 55.6% of private sector workers, 54.2% of professionals, 48.6% of manual workers, and 35.7% of housewives presented with early stage tumors ( Table 2).…”
Section: Data Analysis Of Different Occupation Groupsmentioning
confidence: 81%
See 2 more Smart Citations
“…A similar trend was observed in the tumor stage distribution. By convention, TNM stages I and II are classified as early breast cancer stages (Li et al, 2011). We found that 55.6% of private sector workers, 54.2% of professionals, 48.6% of manual workers, and 35.7% of housewives presented with early stage tumors ( Table 2).…”
Section: Data Analysis Of Different Occupation Groupsmentioning
confidence: 81%
“…Xi'an is a city located in northwestern China that has a less developed economy. Since the First Affiliated Hospital of Medical College of Xi'an Jiaotong University is a representative hospital of this region (Li et al, 2011), the results of this study may, to some extent, reflect the current situation of areas with a less developed economy within China and thus provide a reference to help the Chinese government to develop a female breast cancer prevention program. Furthermore, as China is a developing country, the results of this study may assist other developing countries to improve their breast cancer prevention strategies.…”
Section: Socio-economic Factors Influencing Tumor Presentation Andmentioning
confidence: 90%
See 1 more Smart Citation
“…As compared with cases in some western countries, patients with breast cancer in Asia including China have their unique epidemiological characteristics and physiological features. For example, there are more patients diagnosed at the younger age, and the density of mammary tissue is higher (Fan et al, 2009;Lee et al, 2009;Han et al, 2011;Li et al, 2011). This leads to the controversy on the application of mammography.…”
Section: Introductionmentioning
confidence: 99%
“…Due to genetic factors, lifestyle, and environmental factors, the incidence of breast cancer increases yearly and is trending toward younger women. It usually has complicated etiology and multiple-organ metastasis (Li et al, 2011;Wei et al, 2013). Its incidence in China has already exceeded that of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%